Perception of carbon capture and utilization - a framing analysis of German-speaking media - Fürst, Kristina; Strunge, Till (Frontiers in Energy Research, 2024)
Carbon dioxide capture and utilization (CCU) technologies are one building block in Germany's industrial decarbonization strategy. With CCU technologies, carbon dioxide emissions are captured from an industrial point source or the ambient air (direct air capture, DAC) and either used directly as an industrial feedstock or transformed and used as a carbon resource in industry. Despite the potential benefits of CCU in decreasing industrial dependency on fossil fuels and decreasing global CO2 emissions, robust empirical evidence of the general public opinion and societal acceptance of carbon capture and utilization technologies is lacking. Here, we studied the German-speaking media discourse as a proxy for the public discussion of carbon capture and utilization (CCU) technologies. We show that CCU technologies are overall framed more positively than negatively. Responsible for the optimistic framing are the two dominant media frames: "climate protection-frame" and "benefit-frame", which are mainly used by scientists and policy actors or representatives from the industry sector respectively.